2009
DOI: 10.1016/j.ejcts.2009.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Biseko® colloidal solution diminishes the vasoreactivity of human isolated radial arteries☆

Abstract: Our results suggest that storage of radial artery in Biseko colloidal solution before coronary artery bypass grafting decreases the sensitivity of the graft to vasoconstriction, thereby decreasing the risk of intra/perioperative graft failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…The explanation of this low endothelial function is that the diseases that determine the reactivity of the arterial wall (hypertension, hypercholesterolemia, diabetes) were found to be severe (see Table 3). This depressed endothelium was similar in the controls and in the levosimendan-treated grafts representing a poor cardiovascular status being comparable to our previous populations of patients undergoing CABG [30,31]. We suggest that the poor endothelial function was not due to a mechanical damage of the blood vessel (atraumatic ultrasound technique, no inflation of the artery) but rather represented a severely diseased population of our patients compared to other centers of cardiac surgery [70][71][72].…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…The explanation of this low endothelial function is that the diseases that determine the reactivity of the arterial wall (hypertension, hypercholesterolemia, diabetes) were found to be severe (see Table 3). This depressed endothelium was similar in the controls and in the levosimendan-treated grafts representing a poor cardiovascular status being comparable to our previous populations of patients undergoing CABG [30,31]. We suggest that the poor endothelial function was not due to a mechanical damage of the blood vessel (atraumatic ultrasound technique, no inflation of the artery) but rather represented a severely diseased population of our patients compared to other centers of cardiac surgery [70][71][72].…”
Section: Discussionsupporting
confidence: 50%
“…Papaverine has been widely used for the prevention of RA vasospasm, however, it was shown to impair endothelial function [29]. We have recently shown that a colloidal solution (Biseko® solution) without the addition of a vasodilator substance was able to diminish contractions to 5-HT while the RA graft retained its maximal vasoconstrictive and vasodilating capacities [30]. Vasodilators other than papaverine have also been used in pre-incubation solutions to minimize perioperative spasm of RA grafts.…”
Section: Coronary Artery Bypass Graft Surgery (Cabg)mentioning
confidence: 99%
See 2 more Smart Citations
“…The concentrations of papaverine varied widely from 30 μmol/L to 2.6 mmol/L. In the present study, we used the middle concentration of 1.0 mmol/L, which is also used in internal thoracic artery grafts [9,[10][11][12][13][14]. In the VG group, 2 mL of VG solution was injected.…”
Section: Protocolmentioning
confidence: 99%